‘Urfi Ḥisāb Position in Determination of Beginning of Month of Qamārīyah in Province Jambi - Najmi, Najmi (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article examines the position of ‘Urfi Ḥisāb in determining the beginning of the month of Qamārīyah according to Nahdatul Ulama (NU), Muhammadiyah, and other religious groups in Jambi. The main problem studied is why do these two mass organizations have different views regarding the position of ‘Urfi Ḥisāb? This article comes from qualitative research using juridical-empirical legal methods. The results of the research show that the position of ‘Urfi Ḥisāb is more focused on determining the start of Ramadan and Shawal than other Lunar months. However, it can also be used for other than these two months by referring to the initial benchmark for determination in the first cycle of ‘Urfi Ḥisāb, namely the benchmark for wukuf on Arafah. The reason they have different views about the position of ‘Urfi Ḥisāb is because this method does not take into account the position and location of the Hilāl (new moon). Artikel ini mengkaji tentang kedudukan Ḥisāb ‘Urfi dalam penentuan awal bulan Qamārīyah menurut Nahdatul Ulama (NU), Muhammadiyah, dan Kelompok agama lain di Jambi. Permasalahan utama yang dikaji adalah mengapa kedua Ormas ini berbeda pandangan tentang kedudukan Ḥisāb ‘Urfi? Artikel ini berasal dari penelitian kualitatif dengan metode hukum yuridis-empiris. Hasil penelitian menunjukkan bahwa yaitu kedudukan Ḥisāb ‘Urfi lebih fokus pada penentuan awal Ramadhan dan Syawal daripada bulan-bulan Kamariah lainnya. Namun demikian dapat juga digunakan untuk selain dua bulan tersebut dengan mengacu pada patokan awal penentuan dalam siklus pertama Ḥisāb ‘Urfi, yakni pada patokan wukuf di Arafah. Penyebab mereka berbeda pandangan tentang kedudukan Ḥisāb ‘Urfi itu karena metode ini sama sekali tidak memperhitungkan posisi dan letak Hilāl (anak bulan).